2021
DOI: 10.2176/nmc.oa.2021-0165
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rate and Shunt Infection Incidence Following Gastrostomy in Adult Patients with an Existing Ventriculoperitoneal Shunt

Abstract: Ventriculoperitoneal shunts (VPS) and gastrostomies are frequently provided in daily practice. This study investigated the incidence of VPS infection and the survival rate among adult patients who underwent gastrostomy at least 1 month after VPS placement. This single-center retrospective cohort study was conducted among patients with a VPS, who underwent a gastrostomy. This procedure was performed on a standby basis after a period of at least 1 month had elapsed since VPS placement. Subsequent VPS infection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Respiratory compromise due to subcutaneous emphysema has been reported in a patient who underwent laparoscopic cholecystectomy on day 10 after VPS placement 8 . Furthermore, in a retrospective cohort‐control study, Mawatari et al reported that performing gastrostomy at least 1 month after VPS placement is safe 32 . None of the five shunt patients in whom we performed laparoscopic cholecystectomy underwent shunt intervention and none experienced a shunt‐related complication.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Respiratory compromise due to subcutaneous emphysema has been reported in a patient who underwent laparoscopic cholecystectomy on day 10 after VPS placement 8 . Furthermore, in a retrospective cohort‐control study, Mawatari et al reported that performing gastrostomy at least 1 month after VPS placement is safe 32 . None of the five shunt patients in whom we performed laparoscopic cholecystectomy underwent shunt intervention and none experienced a shunt‐related complication.…”
Section: Discussionmentioning
confidence: 77%
“…8 Furthermore, in a retrospective cohort-control study, Mawatari et al reported that performing gastrostomy at least 1 month after VPS placement is safe. 32 None of the five shunt patients in whom we performed laparoscopic cholecystectomy underwent shunt intervention and none experienced a shunt-related complication. Nevertheless, it seems prudent to allow at least 1 month between shunt placement and laparoscopic cholecystectomy.…”
Section: Analysis Of Perioperative Shunt Managementmentioning
confidence: 91%
See 1 more Smart Citation
“…This review examined thirty-one patients and found only a single case of VPS infection (a rate of 3.2%). They reported no statistically significant difference in infection rates compared to patients who received a VPS without a G-tube (p=0.57) or in survival rates of patients with cerebrovascular disease who underwent a G-tube placement without a VPS [29]. The waiting period recommendation of one month had been found amongst other analyses.…”
Section: Ventriculoperitoneal Shuntmentioning
confidence: 92%
“…To overcome the acknowledged risks associated with a VPS and concurrent PEG tube placement, a waiting period has been suggested. A 2019 retrospective review concluded that a one-month period between VPS placement and G-tube placement was safe in adult patients with an excellent prognosis [29]. This review examined thirty-one patients and found only a single case of VPS infection (a rate of 3.2%).…”
Section: Ventriculoperitoneal Shuntmentioning
confidence: 98%